2020
DOI: 10.3390/su12197898
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Human Resource Development of Convention Project Managers: Job Characteristics and Related Differences in Core Competency

Abstract: There are currently extensive discussions on the remarkable development of the convention industry and the impact on local economies made by convention visitors, but there is limited research on the human resources expertise which is crucial for sustainable and qualitative development in the field of convention. This study aims to examine differences in core competencies based on the type of job characteristics model of convention project managers. Based on the existing literature, quantitative and qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The item "project director has sufficient background, knowledge and skills in project planning" recorded the highest mean of 4.24 (84.8%). In his study, Yoon et al (2020) stated that project directors need to have a set of competencies that enable them to plan and implement projects effectively which supports this study's findings. Meanwhile, "the project director item identifying the knowledge and skills of each project team member" recorded the lowest mean of 3.99 (79.8%).…”
Section: Human/personnel Factorsupporting
confidence: 76%
See 1 more Smart Citation
“…The item "project director has sufficient background, knowledge and skills in project planning" recorded the highest mean of 4.24 (84.8%). In his study, Yoon et al (2020) stated that project directors need to have a set of competencies that enable them to plan and implement projects effectively which supports this study's findings. Meanwhile, "the project director item identifying the knowledge and skills of each project team member" recorded the lowest mean of 3.99 (79.8%).…”
Section: Human/personnel Factorsupporting
confidence: 76%
“…Competencies refer to the abilities, knowledge, and skills of an individual (Ulrich, 1995). Yoon et al (2020) stated that project managers need to have a set of competencies that enable them to plan and implement projects effectively. These competencies also apply to the entire project team (Puthamont & Chareonngam, 2007).…”
Section: Human/personnel Factor At the Project Planning Stagementioning
confidence: 99%
“…In terms of projects, a project manager needs to have a certain set of competencies that will allow them to plan and execute projects effectively. Moreover, it is suggested that not only the project manager, but also the whole project team, must have a certain level of competency in order to complete the project [72]. Furthermore, it is argued in the literature that competency and personality traits potentially produce significant results in projects [73].…”
Section: Project Managers Competenciesmentioning
confidence: 99%
“…Competence is a personality trait (characteristic), which becomes a characteris-tic, and the minimum experience in this area (Yoon et al, 2020). Source competence is a set of general (universal) methods of action that allow a person to understand the situation, achieve results in personal and professional life in the context of specific professional and social partnerships.…”
Section: Competence Typesmentioning
confidence: 99%